Exchange rate policies, prices, and supply-side response : a study of transitional economies - Papazoglou, Christos; Pentecost, Eric J. (New York : Palgrave, 2001)
Examines alternative types of exchange rate policies being pursued and the changing nature of exchange rate policy during the transition process in four countries--Slovenia, Bulgaria, Poland, and the Czech Republic. The book brings together a series of original contributions by country experts and draws out some common themes and over-arching policy implications for the operation of exchange rate policy in the transition process.
Includes bibliographical references (p. 188-195) and index.
oif 29/07/15
Loan
Keywords: Foreign exchange rates- Europe,central; Foreign exchange rates- Europe,Eastern; Foreign exchange administration - Europe,central; Foreign exchange administration- Europe,Eastern